Evaluation of a technical information systems module for distance learning during the COVID-19 pandemic - Arun Aryal; Shilpa Balan (Journal of Research in Innovative Teaching & Learning, 2023)
Purpose – In the wake of the pandemic (COVID-19) throughout the United States, many educators had to promptly switch to online modality to continue to provide education to students with safety through physical distancing requirements. This study mainly focuses on delivering an Information Systems module aligned with the information systems curriculum model during a pandemic. Design/methodology/approach – The authors used data collection techniques from student assignments and course tasks. These data are used for the purpose of academic assessment for the Information Systems program. The student performance is assessed on a 5-point scale (1 being low and 5 being high) for the synchronous and the asynchronous tasks related to the course. The authors compared the student performance during the pandemic to the pre-pandemic semester. Findings – This study revealed that the technical module of an information systems course can be successfully delivered during a pandemic in a remote session. However, the authors found that there is a decline in the student performance in synchronous tasks and asynchronous tasks. But the decline of the student performance in the synchronous tasks is greater than that of the asynchronous tasks. The result of this study helps the Information Systems program with their assessment and to improve their course delivery during a pandemic. Originality/value – In this paper, the authors examine the delivery of a technical module in the field of information systems via online learning models. The authors particularly examine the synchronous and asynchronous online learning models in the delivery of the technical module. The lessons learned from transitioning to the online modality can help universities better prepare for the future during unprecedented times.